Keterampilan Pustakawan Dalam Pengolahan Koleksi Dengan Memanfaatkan SLiMS di UPT Perpustakaan Universitas Pasundan - Oman Rohman; Oom Nurrohmah; Tansah Rahmatullah (Nusantara Journal of Information and Library Studies (N-JILS), 2022)
This research is motivated by the fact that information technology in the university library system has a role to assist librarians in carrying out their roles and functions. With the implementation of SLiMS in the management of the library system, especially in processing collections, it is expected to improve the performance of librarians as an important part of the education system. The results showed that the librarian of the collection processing department in utilizing SLiMS was basically quite skilled. From the results of the study, it can be concluded that the skills of librarians in using the SLiMS bibliography module can be said to be skilled, because SLiMS can help work without any difficulties in its operation. The librarian's skill in using the SLiMS added new bibliography feature can be said to be skilled, because SLiMS is very helpful in doing data entry for new collections quickly and easily. The librarian's skills in verifying bibliographic data always use the bibliographic list sub menu and the exemplar data sub menu in deleting or editing the bibliographic data available in the SLiMS database. The obstacles experienced by librarians in bibliographic data entry are determining the title of the main entry for works written by more than three people, adaptations, editors, and corporate body works.Keywords: librarian skills, bibliographic data entry, SLiMSABSTRAK Penelitian ini dilatar belakangi oleh suatu kenyataan, bahwa teknologi informasi pada sistem perpustakaan perguruan tinggi memiliki peranan untuk membantu pustakawan dalam menjalankan peran dan fungsinya. Dengan diterapkannya SLiMS pada pengelolaan sistem perpustakaan khususnya dalam pengolahan koleksi diharapkan dapat meningkatkan kinerja pustakawan sebagai salah satu bagian penting dalam sistem pendidikan. Hasil penelitian menunjukkan, bahwa pustakawan bagian pengolahan koleksi dalam memanfaatkan SLiMS pada dasarnya cukup terampil. Dari hasil penelitian dapat disimpulkan, bahwa keterampilan pustakawan dalam memanfaatkan SLiMS modul bibliografi dapat dikatakan terampil, karena SLiMS dapat membantu pekerjaan tanpa adanya kesulitan dalam pengoperasiannya. Keterampilan pustakawan memanfaatkan SLiMS fitur tambah bibliografi baru dapat dikatakan terampil, karena SLiMS sangat membantu dalam melakukan entri data koleksi baru dengan cepat dan mudah. Keterampilan pustakawan dalam melakukan verifikasi data bibliografi selalu menggunakan sub menu daftar bibliografi dan sub menu data eksemplar dalam menghapus atau mengedit data bibliografi yang tersedia di dalam database SLiMS. Hambatan yang dialami oleh pustakawan dalam entri data bibliografi adalah menentukan tajuk entri utama karya yang ditulis oleh lebih dari tiga orang, karya saduran, karya editor, karya badan korporasi.